2012
DOI: 10.1371/journal.pone.0048642
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chromosome Segment Substitution Lines in Peanut (Arachis hypogaea L.) Using a Wild Synthetic and QTL Mapping for Plant Morphology

Abstract: Chromosome segment substitution lines (CSSLs) are powerful QTL mapping populations that have been used to elucidate the molecular basis of interesting traits of wild species. Cultivated peanut is an allotetraploid with limited genetic diversity. Capturing the genetic diversity from peanut wild relatives is an important objective in many peanut breeding programs. In this study, we used a marker-assisted backcrossing strategy to produce a population of 122 CSSLs from the cross between the wild synthetic allotetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 35 publications
2
75
0
Order By: Relevance
“…Therefore, these four QTLs were repeatedly detected in different populations. With respect to the QTLs for plant-type-related traits, no similar segment was found between our study and previously studies [26,27,55,56]. …”
Section: Discussionsupporting
confidence: 68%
“…Therefore, these four QTLs were repeatedly detected in different populations. With respect to the QTLs for plant-type-related traits, no similar segment was found between our study and previously studies [26,27,55,56]. …”
Section: Discussionsupporting
confidence: 68%
“…A few more nuclear and cytoplasmic genes were later identified by the same group and those researchers concluded that cytoplasmic inheritance has a major effect on the branching habit of peanut (Ashri, 1975; Ashri and Levi, 1975). In more recent studies, the branching habit trait was genetically characterized and mapped by using inter-specific crossing system with an amphidiploid species (Fonceka et al, 2012a,b). The branching habit trait was phenotyped quantitatively by using a continuous scale from 1 (procumbent) to 6 (erect).…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic allotetraploids that have been produced by crossing different diploid species have proven to be cross-fertile with A. hypogaea (Mallikarjuna et al, 2011). Moreover, the development of peanut genomics tools has made possible the marker-assisted introgression of wild genes into a cultivated background (Fonceka et al, 2012). …”
Section: Introductionmentioning
confidence: 99%